Systematic review of economic evaluations of children's social care interventions. (February 2021) - El-Banna, Asmaa; Petrou, Stavros; Yiu, Hei Hang Edmund; Daher, Shahd; Forrester, Donald; Scourfield, Jonathan; Wilkins, David; Evans, Rhiannon; Turley, Ruth; Wallace, Sarah
Highlights: Economic evaluations of children's social care interventions are limited. Cost-effectiveness and cost-consequence analyses are methods to adopt. The majority of children's social care interventions are considered cost-effective. Priority should be given to developing children's social care outcome measures. Abstract: Background: Children's social care/child welfare services, are under pressure to maximize the value of resource expenditure in meeting the needs of children and young people exposed to risk factors for care entry or residing in care. Economic evaluations can support the decision to adopt, routinize or discontinue an intervention, informing the allocation of limited resources. There is a paucity of economic evaluations in children's social care, partly because this is an emerging area, hence topic-specific methods are lacking. Prior to the development and recommendation of methods, it is important to systematically synthesize those adopted to highlight challenges that have arisen and guide future research. Objective: To assess the methods applied and the cost-effectiveness evidence generated by economic evaluations of children's social care interventions. Methods: Searches of electronic databases and websites were carried out to identify full economic evaluations of children's social care interventions in journal articles and the grey literature. A narrative synthesis of methods adopted and cost-effectiveness results is presented. Results: Twenty studies were eligible for inclusion. These covered parenting programs (n = 8), in addition to a diverse range of other interventions. Cost-effectiveness analysis was the most common approach taken (n = 17) and a large number of studies concluded that the intervention was cost-effective (n = 14). Conclusion: The number of published economic evaluations of children's social care interventions is limited. The available evidence supports the adoption of several of the interventions evaluated, however, the review highlighted a number of challenges in the use of standard economic evaluations methods in this area.